Constraints of Anisotropy on Warm Power-Law Ination in Light of Planck Results - Zahra Ghadiry; Ali Aghamohammadi; Abdollah Refaei (Iranian Journal of Astronomy and Astrophysics)
In this article, we examine the effects of anisotropy on a model of canonical warm inflation with the power-law potential. And we have compared the limitations of this model with Planck's results. Using a conventional local scalar field in the Bianchi type I metric, we have estimated the slow-roll conditions and the suitable regions in which the specific free parameters obtained from the theoretical calculations are in good agreement with the Planck results. Here, as is the usual calculation method in warm inflation, we examine the early universe in two different dissipative regimes, including the weak dissipative regime and the strong dissipative regime, and obtain the field equations. Then we calculate the slow-roll parameters and observational indexes in both regimes and finally, we show that this model has been able to make a good agreement by comparing the theoretical results and observational data obtained from cosmic microwave background and Planck satellites 2013 and 2015